Water resources of the Chad Basin Region - Franklyn R. Kaloko (Faculty of Geography, Universitas Gadjah Mada, 1988)
River basin development is seen as a very effective means of improving agricultural productivity. In the Chad Basin area of the Sahelian Zone of the West African Sub-Region, the water resources have been harnessed to ensure viable agricultural programmes for Nigeria. However,the resultant successes have met by many problems that range from physical to socio-economic and of which water losses have been the most threatening. The study has called for the use of Hexa.deconal (C1-OH) film on the water surface of the Chad as a means of reducing evaporation.